Pengungkapan Aset Biologis, Ekonomi Global dan Hilirisasi Dapatkah Dewan Mendorong Pertumbuhan Berkelanjutan di Industri Agrikultur - Suhardjo, Iwan; Suparman, Meiliana; Rosana, Jackie; Pangestu, Krisnawati Yeni; Rahman, Padli (Politeknik Ganesha Medan, 2024)
Indonesia is an agricultural country where the agricultural sector contributes significantly to GDP. The agricultural sector also plays an important role in providing employment, making it one of the important sectors in the country's economic growth. The purpose of this study is to investigate the impact of biological asset disclosure, downstream practices, and global economic factors on the sustainable growth of agricultural companies in Indonesia, as well as to test the role of board education background in moderation. The research method uses panel data analysis of annual reports of agricultural companies on the Indonesia Stock Exchange (2017-2022) with regression using SPSS Statistics 27. The results show that biological asset disclosure has a significant negative impact on sustainable growth, while downstream practices and global economic factors make significant positive contributions. Meanwhile, the board's educational background was found not to moderate the relationship between biological asset disclosure, downstream, and the global economy on the level of sustainable growth. This study provides in-depth insights into the factors affecting sustainable growth in the Indonesian agricultural corporate sector, with practical implications for corporate strategy and agricultural sector policy.